SECOND-GENERATION TYROSINE KINASE INHIBITORS (TKI) AS SALVAGE THERAPY FOR RESISTANT OR INTOLERANT PATIENTS TO PRIOR TKIs - Breccia, Massimo; Alimena, Giuliana (Mediterranean Journal of Hematology and Infectious Diseases, 2014)
With the advent of target therapies, imatinib became the mainstay for treatment of chronic myeloid leukemia. However, despite the brilliant results obtained with this drug, more than 30% of patients discontinue therapy in long-term due to several reasons, including failure and/or intolerance. Second-generation tyrosine kinase inhibitors (TKIs) are more potent drugs and have expanded inhibition against a broad spectrum of mutations resistant to imatinib. Both nilotinib and dasatinib have demonstrated in vitro and in vivo clinical activity against different types of mutations and various forms of resistance. However, patients with T315I mutation do not obtain an advantage from these drugs and a third generation inhibitor ponatinib, a pan-BCR drug, was tested with significant results. In this review, we report the results of second- and third-generation TKIs tested as second or third line therapy in patients resistant and/or intolerant to previous inhibitors.